2014
DOI: 10.1016/j.gie.2013.09.020
|View full text |Cite
|
Sign up to set email alerts
|

In vivo endomicroscopy improves detection of Barrett's esophagus–related neoplasia: a multicenter international randomized controlled trial (with video)

Abstract: BACKGROUND Confocal laser endomicroscopy (CLE) enables in vivo microscopic imaging of the gastrointestinal tract mucosa. However, there are limited data on endoscope-based eCLE for imaging Barrett’s esophagus (BE). OBJECTIVE To compare high definition white light endoscopy alone (HDWLE) with random biopsy (RB) and HDWLE+eCLE and targeted biopsy (TB) for diagnosis of BE neoplasia. DESIGN Multicenter randomized controlled trial. SETTING Academic medical centers. PATIENTS Adult BE patients undergoing rout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
130
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(138 citation statements)
references
References 31 publications
(40 reference statements)
1
130
0
7
Order By: Relevance
“…This technique also showed good performance for the diagnosis of BE associated neoplasia, with a sensitivity and specificity of 92.9% and 98.4% respectively (49). Moreover, additional studies have shown that the use of eCLE with targeted biopsies has a higher diagnostic yield for BE associated neoplasia compared to standard biopsy protocol, with reduction in the number of biopsies needed (50,51). Real-time microscopic visualization of the mucosa is also achieved with the use of endocytoscopy, however its use has been limited in the management of BE patients due to poor image quality (48).…”
Section: Diagnosis Of Bementioning
confidence: 94%
“…This technique also showed good performance for the diagnosis of BE associated neoplasia, with a sensitivity and specificity of 92.9% and 98.4% respectively (49). Moreover, additional studies have shown that the use of eCLE with targeted biopsies has a higher diagnostic yield for BE associated neoplasia compared to standard biopsy protocol, with reduction in the number of biopsies needed (50,51). Real-time microscopic visualization of the mucosa is also achieved with the use of endocytoscopy, however its use has been limited in the management of BE patients due to poor image quality (48).…”
Section: Diagnosis Of Bementioning
confidence: 94%
“…Recently, confocal laser endomicroscopes (CLE) have been developed that allow magnifications of 1000Â with 1-micron resolution, enabling visualization of cellular and subcellular structures in vivo in real time. [1][2][3][4] Through the use of vascular and molecular contrast agents, multiple structural and functional events can be directly observed, including angiogenesis and monoclonal antibody-antigen binding to epithelial targets. 5 In aggregate, these technologies have opened new fields of endomicroscopy and functional imaging of the GI tract at cellular and subcellular level.…”
mentioning
confidence: 99%
“…Previously explored applications of these new CLE technologies include detection and classification of neoplasia in the colonic polyps, 6,7 inflammatory bowel disease, 8,9 Barrett's esophagus, 1 and the stomach. 10 Molecular imaging with tagged monoclonal antibody has enabled imaging of antiendothelial growth factor receptor monoclonal antibody binding to targets and predication of response to endothelial growth factor receptor chemotherapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, confocal endomicroscopy (CLE) has been used in cancer surveillance in inflammatory bowel disease and in Barrett's esophagus due to its ability to target endoscopic pinch biopsies to dysplastic mucosa [1,2]. Kiesslich et al reported that the use of CLE targeting increased the proportion of dysplasia-positive biopsies while decreasing the overall number of biopsies collected compared with conventional untargeted biopsy acquisition.…”
mentioning
confidence: 99%